#### Answer

The solution is $(6, 11)$.

#### Work Step by Step

We can use the first equation to substitute for $y$ in the second equation. Then we can solve for $x$ first:
$2x - 1 = 3x - 7$
Move the $x$ terms to the left side of the equation by subtracting $3x$ from each side of the equation:
$-x - 1 = -7$
Move constants to the right side of the equation by adding $1$ to each side of the equation:
$-x = -6$
Divide each side of the equation by $-1$ to solve for $x$:
$x = 6$
Now that we have the value of $x$, let's plug this value for $x$ into the first equation:
$y = 2(6) - 1$
Multiply first to simplify:
$y = 12 - 1$
Subtract to solve:
$y = 11$
The solution is $(6, 11)$.